Bibliometric analysis of review on curriculum reform of design history using CNKI database - Huang, Sihua; Mohd Ali, Noor Azizi; Mat Noor, Mohd Sallehuddin; Shaari, Nazlina (Intellect, 2021)
There has been a significant gap in the comprehensive literature review of teaching reform of design history in the Chinese context. In order to bridge this gap, the literature bibliometric method is adopted to review the existing research on design history curriculum reform based on the CNKI database. A keyword review perspective was used to clarify the existing topics in this field, as well as the hotspots of research. Our results reveal that design history, industrial design history and teaching reform are the three main topics that Chinese scholars are more concerned with. As a specific discipline of design history curriculum, curriculum reform of industrial design history is the hotspot of existing research, and teaching reform is an influential research direction.